Who moved my cheese? an amazing way to deal with change in your work and in your life - Johnson, Spencer (New York Putnam, 1998)
Dr. Spencer Johnson realizes the need for finding the language and tools to deal with change -- an issue that makes all of us nervous and uncomfortable. Most people are fearful of change because they don't believe they have any control over how or when it happens to them. Since change happens either to the individual or by the individual, Johnson shows us that what matters most is the attitude we have about change. When the Y2K panic gripped the corporate realm before the new millennium, most work environments finally recognized the urgent need to get their computers and other business systems up to speed and able to deal with unprecedented change. And businesses realized that this was not enough: they needed to help people get ready, too. Johnson has created this book to do just that, containing a simple story with a message that can radically alter the way we cope with change. Who Moved My Cheese? allows for common themes to become topics for discussion and individual interpretation
Parts of all of us -- Story behind the story / Kenneth Blanchard -- Gathering: Chicago -- Story of Who moved my cheese? -- Discussion: later that same day.
79027
Keywords: Change (Psychology); Adaptation, Psychological; Life Change Events